1994
DOI: 10.1128/mcb.14.11.7285
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors NF-IL6 and CREB recognize a common essential site in the human prointerleukin 1 beta gene.

Abstract: A site located between -2782 and -2729 of the human prointerleukin-1o (IL1B) The prointerleukin-1 (proIL-l1,) gene coding for the IL-1,P precursor protein (referred to here by its genomic locus name, IL1B) has been previously reported (10) to be rapidly and transiently transcribed in monocytes by lipopolysaccharide (LPS). The immediate-early transcription of this gene in the absence of protein synthesis (10) strongly supports a mechanism by which one or more preexisting transcription factors is activated. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 48 publications
6
104
1
Order By: Relevance
“…For example, two groups have reported the targeted disruption of the c/ebp␤ gene (51,52) and have shown that this mutation has only minor effects on the expression of inflammatory cytokine genes. These results are surprising in light of previous data showing that C/EBP␤ plays a critical role in the expression of genes such as interleukin-1, interleukin-6, and monocyte chemoattractant protein-1 in cell lines (26,(53)(54)(55), and suggest that a redundant C/EBP activity compensates for the absence of C/EBP␤ in knockout animals. To demonstrate that the compensatory activity is provided by another member of the C/EBP family, one could create DN transgenic mice that express the C/EBP inhibitor specifically in hepatocytes or monocytic cells.…”
Section: Discussioncontrasting
confidence: 51%
“…For example, two groups have reported the targeted disruption of the c/ebp␤ gene (51,52) and have shown that this mutation has only minor effects on the expression of inflammatory cytokine genes. These results are surprising in light of previous data showing that C/EBP␤ plays a critical role in the expression of genes such as interleukin-1, interleukin-6, and monocyte chemoattractant protein-1 in cell lines (26,(53)(54)(55), and suggest that a redundant C/EBP activity compensates for the absence of C/EBP␤ in knockout animals. To demonstrate that the compensatory activity is provided by another member of the C/EBP family, one could create DN transgenic mice that express the C/EBP inhibitor specifically in hepatocytes or monocytic cells.…”
Section: Discussioncontrasting
confidence: 51%
“…The human proIL-1␤ gene contains several cis-acting elements that are required for transcription of the gene. These included the binding sites for Spi-1, C/EBP/NF-IL6, AP-1, and C/EBP-CREB heterodimer (43)(44)(45). Baldassare et al (46) reported that p38 induced transcription of the IL-1␤ gene by acting through C/EBP/NF-IL6.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because C/EBP␤ has been shown to interact with other transcription factors, including Sp1, NF ␤, and CREB, in addition to other members of the C/EBP family. [38][39][40][41] Moreover, the state and site of phosphorylation of C/EBP␤, and of the transcription factors that interact with it play a key role in modulating their transcriptional activity. [42][43][44] Based on the results presented in this communication, as well as others presented elsewhere, 22,36 we propose the hypothesis that agents that induce the accumulation of H 2 O 2 , and/or enhanced binding of C/EBP␤, can be potentially fibrogenic and, thus, could induce the transcriptional activation of the col1a1 gene in HSC.…”
Section: Discussionmentioning
confidence: 99%